Integration And Contribution Of Boarding School Education To Increasing The Quality Of School Education - Yayan Herdiana, Nurwajah Ahmad EQ, Andewi Suhartini (Universitas Pakuan, 2023)
Islamic boarding schools are the oldest educational institutions in Indonesia. The development of Islamic boarding schools is quite tough, because Islamic boarding schools are strong in maintaining traditions while the community wants progress. The robustness of the pesantren in developing its tradition can be seen from the steady curriculum and learning system used. In order to transform a pesantren which consistently maintains its traditionalism, integration of modern education must be carried out which does not change the typical order of the pesantren. This paper wants to find out how the response of salafiyah pesantren to the education integration program. This research is a library research with a descriptive-qualitative approach. Data based on the results of studies on previous research studies were analyzed based on content analysis. As a result, the integration of pesantren education and schools as general educational institutions has mapped pesantren into combination pesantren. There are many benefits and advantages of this integration process, including improving the quality of RAW input, process, output and instrumental input.